Effects of Different Macromolecule Absorbent Resins on the Moisture Characteristics of Major Soil Type on Loess Plateau - Yang, Yong-Hui; Wu, Ji-Cheng; Zhao, Shi-Wei (Asian Journal of Chemistry, 2014)
In order to verify the effects of different macromolecule absorbent resins [PAM (polyacrylamide), PAA (sodium polyacrylate), Wote super absorbent] on the water characteristics of Heilu soil, the major type of soil on the Loess Plateau. We studied the effects of different macromolecule absorbent resins on the soil moisture characteristic curve, water retention ability, water furnishing ability, water transmitting ability and evaporative resistance. The application of different macromolecule absorbent resins into the soil improved the water retention ability and water furnishing ability of the soil and promoted the increase of availability of soil moisture. In addition, it also improved the soil moisture constant and reduced the evaporation capacity of the soil. Among the various applications, the application with 0.212 mg/kg of sodium polyacrylate was the most ideal choice for improving the water retention and water furnishing abilities and increasing the availability of soil moisture of Heilu soil among various macromolecule absorbent resins.